Financial literacy and personal financial planning among the households of migrant workers in Rainas Municipality, Lamjung, Nepal (Journal of Innovation in Academia, 2025)
The aim of this study is to identify the different factors that affect personal financial planning among migrant households. The study employs an explanatory research design to examine the relationship between various factors that influence the personal financial planning of migrant households. It utilizes a purposive sampling method, collecting data from 100 respondents across 10 wards in Rainas Municipality, along with 10 randomly selected respondents. Data is collected through Google Forms and analyzed using SPSS (version 21), SPSS AMOS, and MS-Excel. The results reveal that the majority of households earn around 45,000 to 60,000 per month, indicating a healthy income inflow. The structural equation modeling (SEM) analysis shows that financial awareness (β= 0.218, P0.05) and financial attitude (β= 0.044, P